Analisis Swot Dalam Perencanaan Strategi Pemasaran Umkm Juragan Pisang 99 di Pangkalpinang - Mirna Mirna; Jennie Rorensia; Kurniawan; Indah Noviyanti (Jurnal Manuhara : Pusat Penelitian Ilmu Manajemen dan Bisnis, 2024)
The purpose of this research is to understand and evaluate the marketing strategies implemented by the UMKM Juragan Pisang 99. This research uses a qualitative approach with SWOT analysis, and data collection is conducted through interviews with the company's manager and direct observation. The results are then analyzed using SWOT analysis to identify the strengths, weaknesses, opportunities, and threats of the marketing strategies faced by the UMKM Juragan Pisang 99.